ARGULUS YAWEWITUS SP. N. (CRUSTACEA: BRANCHIURA) PARASITE OF ARAPAIMA GIGAS (SHINZ, 1822) (OSTEOGLOSSIFORMES: ARAPAIMIDAE) FROM BRAZIL - Silva Jtineant, Amanda Karen (2022)
Argulus yawewitus n. sp. is described from pirarucu, Arapaima gigas (Shinz, 1822) from a fish farm in Northeast Brazil. The characteristics that distinguish it from other species are shape of the carapace, abdomen, respiratory areas, the ornamentation and morphology of the antena and antennule, the sexual dimorphism that distinguishes female from male, and the flag-like protrusions on the male’s second and third pair of legs.